New records of Limnonectes rhacodus (Inger, Boeadi and Taufik, 1996) (Lissamphibia: Anura: Dicroglossidae) from Sarawak, East Malaysia (Northwestern Borneo) - Das, I.; Pui, Yong Min; Haas, A. (Check List, 2013)
We comment on the termination of the species nomen of Limnonectes rhacodus (originally described as Rana rhacoda) and report the species from two separate localities in Sarawak State, East Malaysia, based on individuals collected from Kubah National Park, Matang Range and Gunung Penrissen, Padawan, both in western Borneo. The species was previously known from central, western, and southern Kalimantan, Indonesia. These records are the first for Malaysia and extend the distribution range ca. 220 and 264 km northwest of the nearest locality of Bukit Baka-Bukit Raya National Park (West Kalimatan) and increase the species’ elevational range from 500 m to 1,120 m asl.